Performance of tripod foundations for offshore wind turbines: a numerical study. Issue 3 (31st August 2021) - Ochmański, M.; Mašín, D.; Duque, J.; Yi, H.; Lizhong, W.
Abstract : Around 80% of offshore wind turbines (OWTs) are founded on deep seabeds using large-diameter monopiles that reach a length up to 60 m. In a race to seek cost-effectiveness, tripod foundations made with suction caissons represent a promising solution. The deformation mechanism induced by cyclic lateral loading on the tripod bucket embedded in sand reveals recovery of dynamic stiffness with the number of cycles that influences the subsequent dynamic response of the structure–foundation complex. This 'self-healing' and the coupled increase of settlement rate are caused by uneven change in soil fabric and density among the buckets. However, the capability of the recently developed constitutive models to predict this effect is limited. To address this issue, a series of centrifuge tests are herein back-analysed with a three-dimensional finite-element model. The implicit approach has been implemented using an advanced rate-independent hypoplastic model coupled with the conventional intergranular strain theory. The model captures the magnitude of the peak and residual cumulative rotation. The results indicate that the push–pull mechanism turns into a horizontal translation, with active wedges formed behind the pulled bucket. After about 100 cycles, due to significant redistribution of mean stresses, wedges are formed around both pushed and pulled buckets.